Cylindrical spinning rotor gauge — A new approach for vacuum measurement - Almeida, Pedro Gonçalo Dias de (2015)
The spinning rotor gauge (SRG) is one of the most interesting vacuum gauges ever made, covering a pressure range of over seven orders of magnitude, with minimal gas interference (no pumping, ionization or heating of the measured gas), and a great stability of less than 1% drift per year. But despite its remarkable properties, apparently the SRG has not been further developed since the eighties, when it gained commercial interest. In this context, this dissertation aims at providing a starting point for a new line of investigation regarding this instrument, focused on the rotor itself. A brief study of different rotor geometries is provided, including a comparison between a cylindrical rotor and a spherical one. A cylindrical spinning rotor gauge (CSRG) is then proposed, based on the original SRG, but requiring a completely new lateral damping system. A prototype was built and tested against a non calibrated reference gauge.